Forensic value of gunpowder tattooing in identification of multiple entrance wounds from one bullet - Tokdemir, Mehmet; Kafadar, Huseyin; Turkoglu, Abdurrahim; Bork, Turgay (My University, 2007)
Multiple entrance gunshot wounds can give useful information in forensic evaluation of deaths from homicide and suicide. Although the presence of multiple entrance gunshot wounds does not absolutely exclude the possibility of suicide, they are important to the forensic investigators and pathologists in cases of assault, attempted homicide and suicide as they provide important clues for determination of number of shots fired and direction of firing. We present a case of 16 years of young woman who was shot to death by her husband. External examination revealed an entrance wound with semi-lunar shot residue at the dorsal side of her left hand at 5th metacarpus, and exit wound on the hypothenar muscle. There was also a second wound entrance located on her left zygoma. Direction of the bullet was downward traveling from left-to-right. Initially it was thought that there were two close shots, but when her left hand was placed over the malar area her face, it was determined that the gunshot powder tattoos were completing the nature of a single shot from a close distance. Crime scene investigation revealed only one cartridge casing. The autopsy and radiography findings showed that the bullet was entered from dorsal site of the left hand exiting from the palm and re-entering from the zygomatic region, hit the base of the skull, and remained in the soft tissue of the right mandible after passing the soft palate. The bullet was caused an incomplete laceration of the right internal arteria carotid and she died of internal and external bleeding. Detailed investigation of gunshot residues can provide important information for clarification of close distance gunshot wounding. We present this case due to its interesting nature, and to highlight the importance of detailed investigation of the gun powder residues in cases with multiple entry wounds. © 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: Gunshot wound; Powder tattoo; Shot residues; Single bullet-two entrance